2015
DOI: 10.2147/ccide.s75872
|View full text |Cite
|
Sign up to set email alerts
|

An anthropometric study to evaluate the correlation between the occlusal vertical dimension and length of the thumb

Abstract: BackgroundEstablishment of proper occlusal vertical dimension (OVD) is one of the important tasks for successful prosthodontic therapy. An ideal method for determining OVD in terms of cost, time, and instrument requirements has been sought in prosthodontics by various investigators. However, no such single method has been formulated. In the current anthropometric study, the relationship of the length of the thumb to the OVD was tested in two ethnic groups of Nepal, Aryans, and Mongoloids. The result of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 22 publications
(25 reference statements)
1
18
0
4
Order By: Relevance
“…Many authors used various anthropometric measurements to correlate with VDO like fingers, interpupillary distance, hairline to eyebrow line, center of pupil of right eye to center of pupil of left eye, and outer canthus of right eye to the inner canthus of right eye, distance between ear-eye to chin-nose. [10][11][12][13][14][15][16][17][18][19] If an anthropometric correlation is found between the VDO and certain parameters which are easily accessible to the clinician and are static, the time taken for this procedure could be significantly reduced. Also, the conclusions would be objective for every clinician.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors used various anthropometric measurements to correlate with VDO like fingers, interpupillary distance, hairline to eyebrow line, center of pupil of right eye to center of pupil of left eye, and outer canthus of right eye to the inner canthus of right eye, distance between ear-eye to chin-nose. [10][11][12][13][14][15][16][17][18][19] If an anthropometric correlation is found between the VDO and certain parameters which are easily accessible to the clinician and are static, the time taken for this procedure could be significantly reduced. Also, the conclusions would be objective for every clinician.…”
Section: Introductionmentioning
confidence: 99%
“…Ladda et al, 14 found a significant relationship between the VOD and the length of the fingers, the length of the index finger being more reliable for determining the VOD. Basnet et al, 16 actually found a strong correlation between the VOD and the length of the thumb (r=0.874). They also noted correlations between other anthropometric measures such as the distance between the ear tragus and the canthus of the eye, and the edge of the eye-mouth commissure, although these were weak correlations.…”
Section: Resultsmentioning
confidence: 93%
“…13 Lower smile index is another parameter which relates lower facial height and interlabial gap height at smile. 14 Lower facial height was assessed with other facial distances 34 and dental proportions. 20 Interesting fi nding of current study was the ratio of outer intercommissural width to lower facial height was in 1:1 proportion for both groups (ES and US).…”
Section: Discussionmentioning
confidence: 99%